The Imposing Preacher : Samuel DeWitt Proctor and Black Public Faith - Bond, Adam (Book collections on Project MUSE., 2013)
Samuel DeWitt Proctor's voice is essential to understanding the black social gospel. Proctor brought a black middle class understanding of America to his preaching and had a notion of faith that presented an alternative reality to the pervasive racism in the United States and sought to honor the inherent dignity of all humanity.